Producer level cost analysis of the U.S. National Animal Identification System - Crosby, Chris (Kansas State University, 2009)
A Microsoft Excel based budget was developed to find the cost of becoming National Animal Identification Systems (NAIS) compliant in the U.S for beef cow-calf producers. This budget was turned into a stochastic budget by using different distributions for five key variables. From these distributions 10,000 observations were simulated using Latin Hypercube sampling. From the comprehensive budget, a second, more simple budget was constructed for obtaining NAIS cost. This Microsoft Excel based model gives beef cow-calf producers an estimate and a prediction interval associated with the estimated cost of adopting a cattle ID system that is compliant with the National Animal Identification Systems quickly and conveniently, requiring only six inputs. Both the comprehensive and the quick budget are available online. An Ordinary Least Squares regression was estimated using the simulated observations to find marginal effects associated with key variables. The driving factor of total cost per head was eID tag price for operations that tag and eID tag price and chute costs for non-tagging operations. For producers with five or less animals, it was cheaper to hire third parties to tag animals. From the sample data generated, smaller operations pay significantly more than larger operations on a per head basis, as the minimum cost was $2.08 for the larger operations and the maximum cost to small operations was $17.56. The estimated overall average cost per head for the cow/calf industry was $6.26, with a standard deviation of $4.12. Costs were on a per breeding female basis. The Excel spreadsheet budget and model can be downloaded at http://www.agmanager.info/ for producers who wish to estimate NAIS costs specific to their operations.
Keywords: NAIS; National Animal Identification System; NAIS Cost Analysis; eID Cost; Animal Tracing Cost; RFID Cost; Agriculture, Animal Culture and Nutrition (0475); Agriculture, General (0473); Economics, Agricultural (0503)